Etlinger a species of Borneo's wild gingers: Traditional knowledge, phytochemistry, and modern applications - Gilbert Ringgit; Bo Eng Cheong; Muhammad Dawood Shah; Shafiquzzaman Siddiquee (Springer Nature, 2025)
Forty-two (42) Etlinger a species are found in Borneo, commonly known as wild ginger. Of these, 36 species are indigenous to the region, while six species—including Etlinger a coccinea, Etlinger a crispate, Etlinger a elatior, Etlinger a foe ten, Etlin- Gera megachilids, and Etlinger a macrochelids—are also found beyond Borneo. Eight species hold sign if- incant value for local communities, serving roles in traditional medicine, crop production, cosmetics, and personal care. Scientific studies have confirmed six key pharmacological properties in Etlinger a species: anticancer, antidiabetic, antibacterial, antioxidant, pest control, and nephroprotective activities. These bioactivities are attributed to the presence of key bioactive compounds such as b-pinene, 1,7-bis (3,4- dihydroxyphenyl) heptan-3-yl acetate (Etlinger in), curcumin, a-thujene, cyclooctane, and estragole. In modern applications, Etlinger a species are utilized in contemporary cuisine, ornamental horticulture, cosmetics, personal care products, and as natural colorants. This overview underscores the importance of Etlinger a species to local communities and high- lights their relevance in contemporary applications, offering a foundation for identifying species with medicinal and commercial potential in the Borneo region.